Evaluating the potential energy of a heliostat field and solar receiver of solar tower power plants in the southern region of Turkey - Al-Dualimi, Raad Kadhim; SÃ¶ylemez, Mehmet Sait (International Journal of Renewable Energy Development, 2016)
A prior study on the performance of high-efficient models for a heliostat field and solar receiver at various candidate locations (e.g., certain regions in the south of Turkey) helped determine suitable locations for installing solar tower power plant units. This study considered the fact that solar tower power plants are affected by the working conditions of a particular site, which helps realize the highest performance of the solar power tower plant. An optimized heliostat field consisting of 2650 SENER heliostats and a model of a solar receiver based on the data obtained using Gemasolar in Seville, Spain, was used as a reference in this work. Each heliostat position is specified using an optimization algorithm that refines previously proposed models, and two parameters are added to this model to further optimize the heliostat layout. Then, a sample analytical thermal model is used for predicting the radiative and convective heat losses from the receiver system.Â Article History: Received March 13rd 2016; Received in revised form Jun 22nd 2016; Accepted July 3rd 2016; Available onlineHow to Cite This Article: Ra'ad, K, M, A. and Mehmet, S, S. (2016), Evaluating the potential energy of a heliostat field and solar receiver of solar tower power plants in the southern region of Turkey. Int. Journal of Renewable Energy Development, 5(2), 151-161,http://dx.doi.org/10.14710/ijred.5.2.151-161Â